Sistem Pendukung Keputusan Dalam Pemilihan Smartphone dengan Metode SAW - Natanael Dimas Randy; Arita Witanti (STMIK Budi Darma, 2024)
The rapid development of technology in this era has a positive impact on people from various walks of life, including children, adults, and the elderly, who can all benefit from the technology available today. The positive impact of technology includes fast and easy access to information, which can be done anywhere, serving as a learning tool, helping to reduce stress, and even providing income opportunities. Smartphones, or smartphones, are one such technology that is almost owned by everyone because they are sophisticated and practical devices. Due to the increasing demand for smartphones, many companies are striving to produce them. Among the various smartphone brands available, Chinese brands are widely used by Indonesian people due to their competitive prices and specifications in the Indonesian market. The abundance of Chinese smartphones has led to confusion among consumers when choosing a smartphone that suits their needs in terms of specifications and price. In addressing this issue, researchers have developed a website to assist people in choosing smartphones using the Simple Additive Weighting decision support system method. There are 5 criteria and 30 alternatives in this system. People can adjust the criteria values to display results that meet their needs. After the calculation process, the smartphone name Realme 9 obtained a final score of 0.93, making it a viable choice for consumers when purchasing a smartphone.